Content and Bioaccessibility of Aluminium in Duplicate Diets from Southern Spain. Issue 8 (19th August 2013) - Cabrera‐Vique, Carmen; Mesías, Marta
Abstract Aluminium is found naturally in foods and beverages, but levels increase notably during processing, packaging, storage, and cooking, as a consequence of its presence in food additives and the wide use of aluminium utensils and vessels. Dietary intake of Al was estimated in 2 population groups in southern Spain (families and university students) in a duplicate diet sampling study. Diets were sampled for 7 consecutive days, and Al was determined in acid‐mineralized samples with electrothermal atomization‐atomic absorption spectrometry (ETA‐AAS). Mean values for Al intake were 2.93 and 1.01 mg/d in families and students, respectively, ranging from 0.12 to 10.00 mg/d. Assuming an average adult weight of 60 kg, the mean dietary exposures to aluminium were 0.34 and 0.12 mg/kg body weight/week in these groups, which amounted to 17% and 6% of the 2 mg/kg body weight estimated as the tolerable weekly intake by the Joint FAO/WHO Expert Committee on Food Additives. Bioaccessibility of dietary Al tested with in vitro studies ranged from 0.30 to 17.26% (absorbable fraction). The highest aluminium intakes were observed in subjects consuming diets with a low adherence to the Mediterranean diet, which were associated to high consumption of processed and canned food. On the contrary, subjects consuming diets with a high adherence to the Mediterranean diet patterns showed the lowest Al intakes. The present findings are useful for giving both a reliable estimate of total aluminium dietary intake and tolerable intake levels according to usual dietary habits.